2014
DOI: 10.1136/archdischild-2013-304936
|View full text |Cite
|
Sign up to set email alerts
|

'Living with Teenagers': feasibility study of a peer-led parenting intervention for socially disadvantaged families with adolescent children

Abstract: Peer-led parenting groups are feasible and potentially effective for supporting parents of adolescents living in socially disadvantaged communities. These findings warrant more rigorous testing under controlled conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Peer-led interventions have also become increasingly common in child health settings, mostly involving parents but some including young people. Approaches range from structured, manualized programs for groups (eg, EPEC, a parenting program delivered by parents drawn from the local community) 17 to those such as Scope’s “Face to Face,” 18 which trains parents who have had similar experiences (eg, parenting a child with a disability), who then act as befrienders in person, by phone, or email. Positive qualitative outcomes, as identified in a systematic review of peer support for parents of children with disabling conditions, 19 include shared social identity, learning from the experiences of others, and personal growth.…”
mentioning
confidence: 99%
“…Peer-led interventions have also become increasingly common in child health settings, mostly involving parents but some including young people. Approaches range from structured, manualized programs for groups (eg, EPEC, a parenting program delivered by parents drawn from the local community) 17 to those such as Scope’s “Face to Face,” 18 which trains parents who have had similar experiences (eg, parenting a child with a disability), who then act as befrienders in person, by phone, or email. Positive qualitative outcomes, as identified in a systematic review of peer support for parents of children with disabling conditions, 19 include shared social identity, learning from the experiences of others, and personal growth.…”
mentioning
confidence: 99%
“…Only the primary concern was used in analysis, as some parents were unable to nominate three concerns. CAMC is considered to be a sensitive alternative to prolonged direct observation by an independent observer and has been used to assess child outcomes in previous parenting intervention trials (Scott et al, 2001), as well as evaluations of EPEC more specifically (Day et al, 2012; Michelson et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…User satisfaction with EPEC-TA was assessed using the Training Acceptability Rating Scale (TARS). This self-report measure was adapted from previous EPEC evaluations (Day et al, 2012; Michelson et al, 2014), and rates nine items (e.g. ‘Did the group leaders relate to the group effectively?’) on a four-point scale (1 = not at all to 4 = a great deal ).…”
Section: Methodsmentioning
confidence: 99%
“…In comparison, very little research has been conducted on programs targeted specifically at providing parenting support to parents of adolescents, particularly among socially disadvantaged families. One study from the United Kingdom, however, indicated that a program designed specifically to support socially disadvantaged parents of adolescents was feasible and well-accepted by parents (Michelson et al, 2014).…”
Section: Parenting Support Programs As a Solution For Addressing Inte...mentioning
confidence: 99%